Autoimmunity and type 1 diabetes - Cooke, Anne (Henry Stewart Talks, 2021)
Autoimmune disease and associated genes, Autoimmunity usually involves both genetic and environmental factors, Genetic factors of Type 1 diabetes (T1D), environmental factors of T1D, T1D and infection, Infections can either initiate or inhibit onset of autoimmunity, Understanding disease mechanism in order to develop a rational therapy